Analysis of the influence of the FDR, NPF ratio moderated by BOPO on the stability of the performance of Indonesian Islamic banks from early 2020-2023 - Septiawan, Gavinda Micko; Sholahuddin, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
Islam is a religion that prohibits fraud because in any activity must be in accordance with Islamic law, in the banking world it has also formed Islamic banking which has more advantages than conventional banking but with the Covid outbreak, bank performance has declined in Sharia, and conventionally this is highlighted in the bank's financial ratio. Therefore, this study was conducted with the aim of determining the relationship between Financing To Deposit Ratio (FDR), Non Performing Financing (NPF) and Operational Expenses Operational Opinion (BOPO) as moderating variables on Return on Assets (ROA) in Islamic banking in Indonesia during the Covid-19 pandemic. This study uses quantitative methods and uses secondary data using a sample of 11 Islamic banks for the 2020-2023 period which were selected based on being registered with the OJK and using data processing tools in the form of EVIEWS-12 panel data regression for analysis. It can be seen from the results of the t-test that FDR has an effect on the financial performance of Islamic banking, NPF has a significant negative effect on the dependent variable, the effect of variable X1 on the dependent variable is not significant after being moderated, and variable X2 has a significant negative effect on the dependent variable. seen from the results of this study it is recommended to each Islamic bank to ensure that financial performance must remain stable. with the development of the era that exists, it can encourage helping Islamic banking to be known by some people through technology so that Islamic banking can be easily known by many people.